Integration of Sufi Values in Fraud Prevention Efforts: A Conceptual Study in Indonesia - Muhammad Irsyad Elfin Mujtaba; Muhammad Maimun Haki Al Arif; Nur Rohim Al Mahrus Anwar; Imma Rokhmatul Aysa (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose – This study aims to develop an initial conceptual framework that integrates fraud prevention based on Sufi values. This integration is important because the recent rise in moral decadence is considered a serious problem that encourages various types of fraud, including in Indonesia. Design/Methods/Approach – This study uses a library research method with a naturalistic qualitative approach. The emphasis is on critical-analytical thinking about literature and realities related to fraud and its triggers, as well as Sufi values to prevent it from occurring. Findings – The results of this study are the integration of Sufi values in preventing fraud as moral guidelines that shape personal piety and social responsibility. This study also highlights the application of Sufism as ethics in modern life. The values of Sufi teachings can be used as a basis or guideline in building dignified governance while emphasizing that Islamic teachings are a blessing for the entire universe. Research Implications/Limitations – This study only integrates Sufi values in general, without considering the specific characteristics of particular Sufi figures. This study opens opportunities for future research to specifically examine Sufi values by considering the distinctive thought patterns of several well-known Sufi imams embraced by Indonesian society and by communities practicing Sufism. Originality/Value – This study presents an alternative perspective that is able to suppress the factors that drive fraud by strengthening moral values through the integration of Sufi teachings (values).